Maize plant expresses SWEET transporters differently when interacting with Trichoderma asperellum and Fusarium verticillioides, two fungi with different lifestyles - López-Coria, Montserrat; Guzmán-Chávez, Fernando; Carvente-García, Roberto; Muñoz-Chapul, Daniela; Sánchez-Sánchez, Tomás; Arciniega-Ruíz, Juan Manuel; King-Díaz, Beatriz; Sánchez-Nieto, Sobeida (Frontiers in Plant Science, 2023)
Most Trichoderma species are beneficial fungi that promote plant-growth and -resistance, while Fusarium genera causes several crop damages. The biocontrol activity of T. asperellum against F. verticillioides was shown here. Plants in different development stages primed with T. asperellum conidia and challenged with F. verticillioides displayed up-regulated defense-related genes, and sustained chlorophyll content even after the infection. Both fungi affect the expression of several maize sugar transporters differentially; T. asperellum increases the expression of six SWEETs on leaves and two at the roots, and causes a higher exudation of sucrose, glucose, and fructose at the roots. On the contrary, F. verticillioides reduces the expression of the SWEETs on the leaves, and in a severe way when a more aggressive strain is in the plant. Our results suggest that the differences in SWEETs' expression are created once the host plant recognizes the nature and location of the pathogen to establish a new sugar flux.